2017
DOI: 10.16986/huje.2017026950
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Factors Affecting Turkish Students PISA 2012 Mathematics Achievement Using Hierarchical Linear Modeling

Abstract: When Turkey's mathematical literacy performance in PISA 2003 and 2012 is examined, it is seen that it has an increase of approximately 25 points between the two assessments. Despite this increase, the fact that the mathematics performance is below the OECD average leads to the need to determine what factors affect the mathematics performance of Turkish students. This study is aimed to investigate the factors affecting mathematics performance of Turkish students at school and school level. Initially Turkish sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…For example, Ong et al (2010) have also reported that the characteristics of the families is the most important factor affecting academic failure of primary school students in Malaysia. One of the most important factors affecting failure in science courses was the lack of private bookshelves, and this result is in line with the results of the studies conducted by Erbaş (2005), Özer and Anıl (2011) and Saşmazer (2006); in addition, the lack of computers and Internet was in line with the results of the studies by Özer and Anıl (2011) and Christman and Badgett (1999). This may be indicative that the use of technology in science education in Malaysia is particularly effective.…”
Section: Discussionsupporting
confidence: 81%
“…For example, Ong et al (2010) have also reported that the characteristics of the families is the most important factor affecting academic failure of primary school students in Malaysia. One of the most important factors affecting failure in science courses was the lack of private bookshelves, and this result is in line with the results of the studies conducted by Erbaş (2005), Özer and Anıl (2011) and Saşmazer (2006); in addition, the lack of computers and Internet was in line with the results of the studies by Özer and Anıl (2011) and Christman and Badgett (1999). This may be indicative that the use of technology in science education in Malaysia is particularly effective.…”
Section: Discussionsupporting
confidence: 81%
“…This finding constituted a reflection of the literature. The studies focusing on PISA results showed that school-level variables were more dominant than student-level variables in terms of variance in outcome variable (Alacacı & Erbaş, 2010;Astrom & Karlsson, 2007;Özberk, Atalay-Kabasakal, & Boztunç-Öztürk, 2017;Üstün, Özdemir, Cansız, & Cansız, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, different models have been developed based on the latest technologies and building on previous work to statistically minimise errors. Multilevel approaches adopted in these models can be grouped into predictive regression (Anıl, 2009;Gülleroğlu, Bilican Demir, and Demirtaşlı, 2014;Thorpe, 2006;Tomul and Çelik, 2009;Xu, 2006;Yıldırım, 2009), structural equation (Akyüz and Pala, 2010;Anıl, 2008;Özer and Anıl, 2011;Usta and Çıkrıkçı-Demirtaşlı, 2014), and hierarchical linear models (Akyüz, 2014;Atar, 2014;Atar and Atar, 2012;Geske et al, 2006;Tavşancıl and Yalçın, 2015). However, in the literature, there are only a limited number of studies which have evaluated student achievement as a latent variable and analysed it based on patterns identified in variables by creating homogenous sub-classes (Finch and Marchant, 2013;Lin and Tai, 2015).…”
Section: Introductionmentioning
confidence: 99%